5-HTTLPR moderates the association between attention away from angry faces and prospective depression among youth. (August 2017) - Jenness, Jessica L.; Young, Jami F.; Hankin, Benjamin L.
Abstract: Attention bias to emotion has been studied as a risk factor associated with depression. No study has examined whether attention bias within the context of measured genetic risk leads to increased risk for clinical depressive episodes over time. The current study investigated whether genetic risk, as indexed by the serotonin-transporter-linked polymorphic region (5-HTTLPR), moderated the relationship between attention bias to emotional faces and clinical depression onset prospectively across 18-months in a community sample of youth (n = 428; mean age = 11.97, SD = 2.28; 59% girls). Youth who attended away from angry emotional faces and were homozygous for the S allele of the 5-HTTLPR polymorphism were at greater risk for prospective depressive episode onset. The current study's findings highlight the importance of examining risk for depression across multiple levels of analysis and demonstrate attention away from threat as a possible point of intervention related to attention bias modification and depression treatment among youth.